2022
DOI: 10.1038/s41598-022-05226-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound does not activate but can inhibit in vivo mammalian nerves across a wide range of parameters

Abstract: Ultrasound (US) has been shown to stimulate brain circuits, however, the ability to excite peripheral nerves with US remains controversial. To the best of our knowledge, there is still no in vivo neural recording study that has applied US stimulation to a nerve isolated from surrounding tissue to confirm direct activation effects. Here, we show that US cannot excite an isolated mammalian sciatic nerve in an in vivo preparation, even at high pressures (relative to levels recommended in the FDA guidance for diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…In Collins et al (2021) , comparable intensities were insufficient to modulate the activity of the spontaneously-firing DE-3 neuron, nor evoke spikes from any of the other neurons whose axons pass through the DP nerve. This is consistent with others’ findings that peripheral nerves, in comparison to central neural tissues, require much more energy to achieve an effect ( Guo et al, 2022 ). Authors Wright et al (2017) averaged intensities used to modulate peripheral nerves across studies, and calculated a mean intensity of 59 W/cm 2 , versus 3 W/cm 2 in CNS studies.…”
Section: Parameter-associated Limitations As a Contributor To The Lac...supporting
confidence: 93%
See 2 more Smart Citations
“…In Collins et al (2021) , comparable intensities were insufficient to modulate the activity of the spontaneously-firing DE-3 neuron, nor evoke spikes from any of the other neurons whose axons pass through the DP nerve. This is consistent with others’ findings that peripheral nerves, in comparison to central neural tissues, require much more energy to achieve an effect ( Guo et al, 2022 ). Authors Wright et al (2017) averaged intensities used to modulate peripheral nerves across studies, and calculated a mean intensity of 59 W/cm 2 , versus 3 W/cm 2 in CNS studies.…”
Section: Parameter-associated Limitations As a Contributor To The Lac...supporting
confidence: 93%
“…In our studies of single identified leech motoneurons, we came to the conclusion that the bioeffects of FUS-mediated neuronal inhibition ( via action potential blockade) were thermally mediated. A parallel study to ours conducted in mammalian peripheral nerves came to the same conclusion that suppression of neural activity was mediated by FUS thermal effects ( Guo et al, 2022 ). In the following section we will outline the FUS stimulus parameters we used to arrive at our conclusions.…”
Section: Parameter-associated Limitations As a Contributor To The Lac...mentioning
confidence: 54%
See 1 more Smart Citation
“…188,189 Due to the excellent focality and steering capacities of FUS-based neuromodulation, US-PNS has been successfully performed in numerous studies in animals and a few human studies showing inhibitory and exhibitory neuromodulation effects. 78,136,[190][191][192] Young and Henneman had already shown in 1961 that US could differentially modulate the activity of Aδ-and C-fibers, depending on the fiber diameter, US intensity, and US exposure time. 193 More recently, additional technical assistance via focal depth controller has been proposed to further improve peripheral nerves targeting for neurorehabilitation 194 , making FUS a very selective method for peripheral nerve stimulation.…”
Section: Peripheral Nerve Stimulation (Pns)mentioning
confidence: 99%
“…Similarly, FUS of the hepatoportal nerve plexus in animal models of diabetes restores glucose homeostasis via activation of TRPA1-positive, afferent nerve fibers (35). Notably, the abovementioned mechanosensitive ion channels are expressed in peripheral ganglia, in the vagus nerve and in some spinal nerves (36); the same channels are not expressed in other peripheral nerves, such as sciatic nerve, in which FUS does not elicit nerve responses (37). Furthermore, we found no evidence of a direct hemodynamic effect of sFUS in the systemic or the pulmonary circulation (Suppl.…”
Section: Mechanisms Of Sfus Neuromodulationmentioning
confidence: 99%